The Training on Creating Innovative Learning Media from Recycled Materials as an Effort to Enhance Teacher and Student Creativity - Prihantini, Prihantini; Hendrilia, Yudi; Abidin, Andi Rahmat; Indrayani, Teti; Azwar, Rica; Walid, Abul; Yantiningsih, Erna (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This community service aims to explore the use of innovative learning media based on recycled materials to enhance the creativity of teachers and students in elementary schools. This activity involved 15 teachers from schools in Padang city, focusing on training in the creation of environmentally friendly and economical learning media. Through this activity, teachers were introduced to practical techniques for utilizing recycled materials such as banana leaves, banana stalks, and used paper to create teaching aids that support interactive and enjoyable learning. The results of the training showed an increase in teachers' creativity in creating effective and environmentally friendly learning media. Additionally, this activity provided new insights into the importance of utilizing available materials to support more sustainable teaching and learning processes. This community service is expected to contribute to improving the quality of education in schools with limited budgets and encourage the creation of a more creative and innovative learning environment.